5 - Family Structure and Children’s Schooling in sub-Saharan Africa - Acheampong Yaw Amoateng,; Tim B. Heaton,; Camille Mcalmont, (African Sociological Review, 2017)
To examine the effect of family structure on children’s schooling in sub-Saharan Africa, we employed Multi-level Modeling to analyse data from recent Demographic and Health Surveys (DHS) in 26 African Countries. In general, both polygyny and presence of a husband in the home detract from children’s education. After controlling for maternal education, children of single, never married mothers and those who are divorced or separated have educational disadvantage, suggesting the importance of maternal education for children’s educational outcomes. Males are more likely than females to have higher educational attainment, especially those in polygynous families. It is recommended that female education in general and the education of the girl-child in particular, be encouraged as a way of discouraging such negative cultural attitudes and practices as polygyny and bias in favour of boys’ education.